Training on Beverage Cost Calculation at Class 2 Correctional Facility Batam - Rezki Alhamdi; Pratama, Tito; Aurora Mikasari, Dewi; Wibowo, Agung Edy; Ulum Lubis, Taufik Bachrul (PUSLITABMAS-Politeknik Pariwisata Batamc, 2025)
This Community Service Program (PKM) aims to enhance the skills of inmates at Lapas Class II Batam in calculating the production costs of beverages. These skills are essential to prepare them for entering the workforce or starting small businesses in the beverage sector after completing their sentences. The training involved lecturers from Politeknik Pariwisata Batam who provided practical knowledge on various components of production costs, such as raw material costs, labor costs, and operational expenses. Inmates were also taught how to determine profitable selling prices and strategies for efficient business management. The training methods included theoretical sessions, practical simulations, and interactive discussions to ensure a deep understanding among participants. The results of the training showed a significant improvement in the inmates’ understanding of production cost management. They were not only able to accurately calculate costs but also grasped financial management concepts that support small business operations. The sustainability of this program is supported by strong collaboration between Politeknik Pariwisata Batam and Lapas Class II Batam, as well as the provision of adequate facilities for training. With the integration of this program into the correctional facility's activities, it is expected that the training will continue and provide long-term positive impacts. In conclusion, this beverage production cost training plays an important role in empowering inmates with relevant skills, helping them adapt to the workforce, and opening up future business opportunities.